Elevated Inorganic Carbon Concentrating Mechanism Confers Tolerance to High Light in an Arctic Chlorella sp. ArM0029B - Hwangbo, Kwon; Lim, Jong-Min; Jeong, Seok-Won; Vikramathithan, Jayaraman; Park, Youn-Il; Jeong, Won-Joong (Frontiers in Plant Science, 2018)
Microalgae and higher plants employ an inorganic carbon concentrating mechanism (CCM) to increase CO2 availability to Rubisco. Operation of the CCM should enhance the activity of the Calvin cycle, which could act as an electron sink for electrons generated by photosynthesis, and lower the redox status of photosynthetic electron transport chains. In this study, a hypothesis that microalgal cells with fully operating CCM are less likely to be photodamaged was tested by comparing a Chlorella mutant with its wild-type. The mutant acquired by screening gamma-ray-induced mutant libraries of Chlorella sp. ArM0029B exhibited Constitutively Active CCM (CAC) even in the presence of additional inorganic carbon sources under mixotrophic growth conditions. In comparison to the wild-type alga, the mutant named to CAC1, showed more transcript levels for genes coding proteins related to CCM such as inorganic carbon (Ci) transporters and carbonic anhydrases (CA), and greater levels of intracellular Ci content and CA activity regardless of whether growth is limited by light or not. Under photoinhibitory conditions, CAC1 mutant showed faster growth than wild-type cells with more PSII reaction center core component D1 protein (encoded by psbA), higher photochemical efficiency as estimated by the chlorophyll fluorescence parameter (Fv/Fm), and fewer reactive oxygen species (ROS). Interestingly, high light induced increase in ROS contents in wild-type cells was significantly inhibited by bicarbonate supplementation. It is concluded that constitutive operation of CCM endows Chlorella cells with resistance to high light partly by reducing the endogenous generation of ROS. These results will provide useful information on the interaction between CCM expression, ROS production, and photodamage in Chlorella and related microalgae.